2018
DOI: 10.14202/vetworld.2018.99-103
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of Jatropha curcas Linn. latex in cream formulation on CD68 expression in mice skin wound

Abstract: Aim:The purpose of the present study was to determine the potential of Jatropha curcas latex in the cream formulation on CD68 immune expression (macrophages) during inflammatory phase wound healing process in mice skin.Materials and Methods:Amount of 12 two-months-old male mice were used between 30 and 40 g. To surgical procedures, wound skin incision was performed 2.0 cm in length until subcutaneous on the paravertebral of each animal. The treatment was carried under locally anesthetized with procaine cream. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 45 publications
3
25
0
1
Order By: Relevance
“…Tannins are included as antinutrients in legumes which inhibit the digestion of protein but are destroyed by cooking to increase the functions of amylase and protease and better protein digestion 29 . Dietary tannins, flavonoids and saponins found in P. vulgaris like other plant sources, are known for their medicinal importance in the preparation of herbal formulation as active constituent to take part in cancer prevention, function as antioxidants and possess antiinflammatory ability 30, 31 . Cooking reduced the content of alkaloids in cooked extract of P. vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…Tannins are included as antinutrients in legumes which inhibit the digestion of protein but are destroyed by cooking to increase the functions of amylase and protease and better protein digestion 29 . Dietary tannins, flavonoids and saponins found in P. vulgaris like other plant sources, are known for their medicinal importance in the preparation of herbal formulation as active constituent to take part in cancer prevention, function as antioxidants and possess antiinflammatory ability 30, 31 . Cooking reduced the content of alkaloids in cooked extract of P. vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…A cream base was added little by little with the 10% and 15% latex of J. curcas in a porcelain dish containing 100 g of cream and stirred until homogeneous at room temperature. The dosages of 10% and 15% latex of J. curcas have been proven to be effective to use for topical for topical wound healing [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The mice skin wound was done by mean of surgical procedures as explained by Salim et al . [ 24 ]. Mice were locally anesthetized by topical cream with containing lidocaine 25 mg and prilocaine 25 mg. Longitudinal wounds of about 2.0 cm were made on the paravertebral region till to subcutaneous under the aseptic condition and were observed throughout the experimental study.…”
Section: Methodsmentioning
confidence: 99%
“…The wounded skin was sampled after the mice were euthanized for conducting histopathological slides. Procedure making histopathological preparations refers to standard methods [12]. The slides were evaluated by staining with Hematoxylin-eosin (HE) and Masson's trichrome (MT).…”
Section: Histopathological Slides Preparationmentioning
confidence: 99%
“…Previously study indicated latex of J. curcas have proven to accelerate the inflammatory phase [12], epithelial phase [13,14], and angiogenesis activity [15]. This causes that the latex of J. curcas effective to be used for topical therapy on wound healing in mice skin.…”
Section: Introductionmentioning
confidence: 99%